Democracy and local government administration in Nigeria - Ganduje, Abdullahi Umar. (Ibadan : Spectrum Books, 2006)
Highlights the problems encountered in local government administration in a democratic set-up and their implications for national development. It also looks at the various factors militating against the attainment of full autonomy by local government and offers practical solutions.
Includes bibliographical references and index.
oif 14/07/14
Loan
Keywords: Local government; Democracy